Aneurysm size and the Windkessel effect: An analysis of contrast intensity in digital subtraction angiography. Issue 4 (August 2017) - Hussein, Ahmed E; Esfahani, Darian R; Linninger, Andreas; Charbel, Fady T; Hsu, Chih-Yang; Charbel, Fady T; Alaraj, Ali
Large cerebral aneurysms are considered more dangerous than their smaller counterparts, with higher risk of subarachnoid hemorrhage. Understanding the hemodynamics of large aneurysms has potential to predict their response to treatment. Digital subtraction angiography images for patients with intracranial aneurysms over a seven-year period were reviewed. Unruptured solitary aneurysms of the internal carotid artery (ICA) proximal to the terminus and posterior communicating artery were included. Contrast intensity over time was analyzed at the center of the M1 segment of the middle cerebral artery distal to the aneurysm and compared to the contralateral side. Analysis included time to peak (TP)10%–100% (time needed for contrast to change from 10% intensity to 100%), washout time (WT)100%–10% (time for 100% intensity to 10%), and quartile time (QT)25%–25% (time for 25% intensity during vessel filling to 25% during emptying). Fifty patients met the inclusion criteria. Analysis over the ipsilateral M1 segment revealed a significant increase in QT25%–25% (8.5 vs 7.6 seconds, p =  0.006) compared to the contralateral side. There was a correlation between TP10%–100% and QT25%–25% with aneurysm size (Pearson's r  = 0.37, p  = 0.007 and r  = 0.43, p  = 0.001, respectively). Larger ICA aneurysms were associated with delayed contrast intensity times . A plausible mechanism is that large aneurysms act as a capacitance chamber (Windkessel effect) that slow the arrival of contrast distal to the aneurysm. This may be of significance for large aneurysms after treatment, where the loss of the Windkessel effect places the distal circulation at greater risk for hemorrhage, and warrants further study.